An experimental study of helium diffusion and helium induced microstructural evolution in ion implanted polycrystalline titanium nitride. (December 2016) - Agarwal, S.; Trocellier, P.; Brimbal, D.; Vaubaillon, S.
Abstract: In this paper, the behavior of helium and its influence on the microstructure in polycrystalline titanium nitride (TiN) is studied by ion implantation technique, coupled with post-implantation annealing experiments between 1273 and 1873 K. The samples were implanted at room temperature with helium up to ∼2.2, 0.25 and 0.07 at. % at the implantation peak, respectively. Helium induced bubble microstructure was characterized using transmission electron microscopy (TEM) which revealed the effect of annealing temperature and helium concentration on the evolution of the bubbles in the material. TEM analysis also revealed that no amorphisation occurred up to the maximum dose level of 0.8 dpa at room temperature, corresponding to the highest implantation level. The technique of nuclear depth profiling using nuclear reaction analysis (NRA) revealed the helium diffusion and retention behavior in the material at different annealing temperatures and helium concentration levels. A sharp increase in helium loss from TiN occurred after annealing beyond 1373 K for the highest helium level, whereas no loss occurred for the lowest implanted helium level. The effective activation energies of helium diffusion and release were estimated utilizing Fick's law of diffusion and 1st order kinetic law, respectively. A novel method of estimating pressure inside bubbles is discussed by utilizing the high-density equation of state, incorporating the experimentally determined helium density, deduced from coupling the result of helium concentration measurement from NRA and vacancy concentration measurement from the experimentally determined size and number density of bubbles from TEM. These results reveal that such kind of calculation technique can be utilized for bubbles formed at higher annealing temperatures. Graphical abstract: